RANCANGAN OBSERVER SISTEM DESKRIPTOR KONTINU - M., Musraini
Abstract : In this paper, we discuss design of observers for linear time-invariant continous descriptor system E*x(t) = A*x(t) + B*u(t) y*(t) = C*x(t) where E*, A*, B*, C* are known constant matrices, but E* is not non singular matrice. In this design of observers is presented for full and reduced-order observers. Next, we also discuss the other method of design of observers, namely using Singular Value Decomposition Theorem.